Electrocautery Maze for Chronic Atrial Fibrilation in Patients Undergoing Mitral Valve Replacement - Reza, Md Mohashin; Hasan, Md Kamrul; Sarker, Rampada; Sarker, Swadesh Ranjan; Hussain, Sabrina Sharmin; Rushel, Khandoker Shamim Shahriar Zibon; Alam, AKM Manzurul (University Heart Journal, 2018)
Aims: The present research aimed at to study of the compartmentalization of the posterior wall of the left atrium by using conventional electrocautery in order to reverting atrial fibrillation in patients undergoing mitral valve replacement Methods: This Quasi experimental study carried out in department of cardiac surgery, National Institute of Cardiovascular Disease (NICVD) and Hospital, Dhaka, Bangladesh. Total 64 patients are taken and then grouped into group A and group B. Each group contains 32 patients. Group A patients who underwent MVR with electrocautery maze Group B Patients who underwent for MVR only. All patients were evaluated continuous and with 12 lead ECG in immediate post-operative period, during discharge. Statistical analysis of the results was obtained by windows based computer software with statistical package for the social sciences program (SPSS version 21). Results: Freedom from atrial fibrillation in group A and group B was 28 (88.6%) and 6 (16.5%) patients at 1month follow up respectively and 11.5% and 75.0% patients AF persist in group A and group B respectively. 1 (3.1%) patient in group B was AF with slow ventricular rate. Conclusion:The finding of this study permit to conclude that the present study showed that the surgical treatment of atrial fibrillation with electrocautery, in mitral valve surgery, was capable of determining the reversion of this arrhythmia in a significant number of patients during a shortterm clinical follow-up, with low mortality and with low morbidity University Heart Journal Vol. 13, No. 2, July 2017; 46-49